PENGARUH PEMAHAMAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN KEGIATAN BISNIS ONLINE DI SURABAYA - Muslimin Muslimin (Behavioral Accounting Journal, 2021)
Tax compliance is the attitude or action of a taxpayer who is obedient to taxation provisions based on the applicable laws. The goals of this research were to prove “the effect of understanding, awareness, and tax sanctions on individual taxpayer compliance who conducts online business activities in Surabaya”. The applied method is using “a quantitative method”. The sample in this research were “taxpayers who do online business” where the whole amount of sample is 100 respondents. The determination of that sample is using “the Probability sampling technique with the Simple Random Sampling technique”. The data collection technique used a mail survey. The findings of this research showed how “the individual taxpayers who do online business in Surabaya” have a high level of compliance when tax sanctions are actually applied. However, on the other hand, the research results have not provided evidence that the level of understanding and awareness of taxes can increase the level of compliance in paying taxes. For this reason, the recommendation that can be given to the tax authorities is that tax sanctions must be strictly implemented so that taxpayers become more obedient.